Caste studies today - Prakash Shah (Oñati Socio-Legal Series)
Starting with an individual report in a leading British periodical of higher education, this article fans outwards to show how the contemporary field of caste studies reflects the degeneracy of its methods and claims. Rather than producing knowledge about India and the so-called caste system, caste studies has worked itself into a corner by creating a set of imagined victims and perpetrators of caste oppression, atrocities, violence and discrimination, and by making unsustainable claims on legal systems and other institutions. The manifold and insurmountable problems of contemporary caste studies include its basis in the European framework for the study of India founded upon Christian theological claims, the carry-over of this account into the secularised humanities and social sciences, and its engagement in corrupted academic practices of the kind that typify grievance studies today. That an alternative account exists in the form of the research programme of SN Balagangadhara, which inspires the articles in this special issue, is good reason for rethinking and revision of the field.